Topofobia e topofilia em “A Terra”, de “Os Sertões”: uma análise ecocrítica do espaço sertanejo euclidiano / Topophobia and topophilia in”The Land” of “Os Sertões”: Analysis ecocriticism of space Sertanejo Euclideano - Edilane Ferreira da Silva; Érika Maria Asevedo Costa; Geraldo Jorge Barbosa de Moura (Sociedade & Natureza)
In 1902, the journalist Euclides da Cunha published the work Os Sertões which, starting Pre-Brazilian Modernism and enhance Bahia´s backlands from the Canudos War. We analyze the chapter “The Earth” of the Euclidean book, in order to examine the discourse method analysis and the ecocriticism perspective - which concerns the interactions between literature and ecology - the author approaches between the backwoods and wilderness, and his own feelings regarding this space, considering topophobia concepts - aversion to physical environment and topophilia - familiarity or attachment, proposed by the chinese geographer Yi-Fu Tuan and related humanistic geography. Thus, the present discourse in the narrative demonstrate predominance of dislikes and horror feelings for the caatinga, regarding the subjectivity of the writer and oikos referenced by him.